The impact of continued intervention on weight: Five‐year results from the weight loss maintenance trial. Issue 5 (15th March 2016) - Coughlin, Janelle W.; Brantley, Phillip J.; Champagne, Catherine M.; Vollmer, William M.; Stevens, Victor J.; Funk, Kristine; Dalcin, Arlene T.; Jerome, Gerald J.; Myers, Valerie H.; Tyson, Crystal; Batch, Bryan C.; Charleston, Jeanne; et al.
Abstract : Objective: In the Weight Loss Maintenance (WLM) Trial, a personal contact (PC) intervention sustained greater weight loss relative to a self‐directed (SD) group over 30 months. This study investigated the effects of continued intervention over an additional 30 months and overall weight change across the entire WLM Trial. Methods: WLM had 3 phases. Phase 1 was a 6‐month weight loss program. In Phase 2, those who lost ≥4 kg were randomized to a 30‐month maintenance trial. In Phase 3, PC participants ( n = 196, three sites) were re‐randomized to no further intervention (PC‐Control) or continued intervention (PC‐Active) for 30 more months; 218 SD participants were also followed. Results: During Phase 3, weight increased 1.0 kg in PC‐Active and 0.5 kg in PC‐Control (mean difference 0.6 kg; 95% CI:−1.4 to 2.7; P = 0.54). Mean weight change over the entire study was −3.2 kg in those originally assigned to PC (PC‐Combined) and −1.6 kg in SD (mean difference −1.6 kg; 95% CI:−3.0 to −0.1; P = 0.04). Conclusions: After 30 months of the PC maintenance intervention, continuation for another 30 months provided no additional benefit. However, across the entire study, weight loss was slightly greater in those originally assigned to PC.